MODERN DIGITALIZATION TRENDS OF GEORGIA AND UKRAINE - Givi BEDIANASHVILI; Hanna ZHOSAN; Sergiy LAVRENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In today's turbulent and unstable environment, international companies, including Ukraine and Georgia, are forced to move to technologies they did not plan to implement for some time and reconsider their strategic priorities. "Become digital or die" is the reality of the COVID-19 epidemic. Companies that will survive in the long run - those that have the best tools that allow them to be flexible, agile, agile; those who are better than others will be able to respond to changes in the product range, control and monitor their factories, regulate supply chains and will be able to use their workforce really anywhere. Mixed research methods were used to analyse the data. The theoretical and methodological basis of the study were the dialectical method of cognition, a systematic approach to the use of general provisions of economic theory. According to the research results, despite the serious positive transformations in the field of digitalization, there are a number of current and significant unresolved issues in the industry. It is established that the digital economy in Ukraine and Georgia, despite a number of existing problems, is developing dynamically. Organizations in various sectors of the economy are beginning to actively implement digital solutions, taking into account the specifics of their activities. Innovation is the engine of economic development, so attempts are made to find and create the most appropriate forms of organizational associations of innovative enterprises, alliances, within which strong cooperative ties can be established. The need for large-scale cooperation and coordination in the form of networking of participants in the innovation process becomes quite obvious, which provides them with a beneficial effect and corresponding competitive advantages.